The brain effects of laser acupuncture in healthy individuals: an FMRI investigation. - Im Quah-Smith (Public Library of Science (PLoS), 2010)
Background As laser acupuncture is being increasingly used to treat mental disorders, we sought to determine whether it has a biologically plausible effect by using functional magnetic resonance imaging (fMRI) to investigate the cerebral activation patterns from laser stimulation of relevant acupoints. Methodology/principal findings Ten healthy subjects were randomly stimulated with a fibreoptic infrared laser on 4 acupoints (LR14, CV14, LR8 and HT7) used for depression following the principles of Traditional Chinese Medicine (TCM), and 1 control non-acupoint (sham point) in a blocked design (alternating verum laser and placebo laser/rest blocks), while the blood oxygenation level-dependent (BOLD) fMRI response was recorded from the whole brain on a 3T scanner. Many of the acupoint laser stimulation conditions resulted in different patterns of neural activity. Regions with significantly increased activation included the limbic cortex (cingulate) and the frontal lobe (middle and superior frontal gyrus). Laser acupuncture tended to be associated with ipsilateral brain activation and contralateral deactivation that therefore cannot be simply attributed to somatosensory stimulation. Conclusions/significance We found that laser stimulation of acupoints lead to activation of frontal-limbic-striatal brain regions, with the pattern of neural activity somewhat different for each acupuncture point. This is the first study to investigate laser acupuncture on a group of acupoints useful in the management of depression. Differing activity patterns depending on the acupoint site were demonstrated, suggesting that neurological effects vary with the site of stimulation. The mechanisms of activation and deactivation and their effects on depression warrant further investigation.